The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7863/jum.2012.31.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Inclination at 14 to 39 Weeks' Gestation in Normal Korean Fetuses

Abstract: Objectives The purpose of this study was to evaluate a normal range for prenatal craniofacial inclination using images of fetal profiles at 14 to 39 weeks' gestation in normal Korean fetuses. Methods We conducted a cross‐sectional study of 308 normal fetuses at 14 to 39 weeks' gestation. After the exclusion of images with inadequate quality, the sagittal plane of the sonographic fetal facial profile from 250 normal fetuses was evaluated. The frontomaxillary facial, frontonasal, maxilla‐nasion‐mandibular, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Both studies have shown that the MNMA is gestational‐age independent, which is its potential advantage over the assessment of FMA and FNMA. However, surprisingly, MNMA measured in normal Korean fetuses from 14 to 39 weeks' gestation was far smaller, with mean only 4.7 ○ ( SD 3.3 ○ ). A significant negative correlation of MNMA with gestational age was also demonstrated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies have shown that the MNMA is gestational‐age independent, which is its potential advantage over the assessment of FMA and FNMA. However, surprisingly, MNMA measured in normal Korean fetuses from 14 to 39 weeks' gestation was far smaller, with mean only 4.7 ○ ( SD 3.3 ○ ). A significant negative correlation of MNMA with gestational age was also demonstrated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that normal reference values of the fetal nasal bone length in Asian populations were shorter than those of white and African American popula‐tions 12 , 24 , 26 . In our previous study about craniofacial inclination during gestation, we showed that the frontomaxillary facial angles of Korean fetuses were greater than the angles of other ethnic fetuses between 14 and 25 weeks' gestation 28 . In addition, in another study dealing with frontomaxillary facial angles in Korean fetuses at the 11 weeks' to 13 weeks 6 days' gestation, it was reported that the overall mean frontomaxillary facial angles were greater than those of other ethnicities 27 .…”
Section: Discussionmentioning
confidence: 74%
“…Recently, we showed the craniofacial inclination of the fetal facial profile in normal Korean fetuses 28 . The aim of this study was to describe the normative sonographic appearance of the fetal facial profile in the exact midsagittal plane by 2D or 3D multiplanar sonography, with particular regard to the nasolabial size by evaluating nose length, nose protrusion, pronasal‐subnasal distance, distance between the upper philtrum and mouth, and distance between the tip of the nose and mouth in normal Korean fetuses during gestation.…”
mentioning
confidence: 99%
“…On the other hand, 2D ultrasound was the basis of 3D ultrasound. 2D measurements were reported to be the same reliable and accurate as 3D measurements in the measurement of facial marker [27,28] .…”
Section: Discussionmentioning
confidence: 91%